Perception of healthcare administrators on the impediments of optimizing adverse events following immunization e-Reporting in Nigeria - Grace Fubara Erekosima; Saheed Dipo Isiaka; Folake Oni; Ahmed Rufai Garba; Oluchi Bassey; Stephen Olabode Asaolu; Olugbemisola Wuraola Samuel; Genevieve Ozioko; Oluwafisayo Azeez Ayodeji; Euphemia Chigekwu Agomuo; Irene Odira Okoye; Sidney Sampson; et al. (PLoS ONE, 2025)
Background Adverse events following immunization (AEFI) are any negative medical event that occurs after vaccination but may or may not be causally related to the vaccine. AEFI reporting is the gateway to AEFI surveillance systems at primary healthcare facilities where immunization services are provided. Several studies have highlighted low reporting of AEFI cases, particularly in low-resource settings, yet nothing is known about stakeholders’ perspectives on the factors associated with the AEFI reporting rate in Nigeria. Objective This study explored the stakeholders’ perspectives (from a baseline assessment) on the barriers to adequately reporting (electronically) AEFI in Nigeria. Methods The study was conducted using a qualitative approach. Key informant interviews were conducted at the national and sub-national (state) levels, who were purposively selected to acquire information from stakeholders on the challenges facing the e-reporting of AEFI at the national and state levels. All the audio interview files were transcribed into English Language, coded, and presented using a thematic approach. Results A total of 32 healthcare workers at the national and sub-national levels participated in the study. The study adapted an extant pharmacovigilance thematized framework of reporting the barriers to electronic reporting of the pharmacovigilance system. Therefore, this study categorized the participants’ responses into four main themes, including healthcare workers’ knowledge deficiency and fear, technical infrastructural challenges, poor reporting systems, and inconsistency in government commitment. Conclusion This study concludes that the AEFI surveillance system in Nigeria requires immediate and thorough attention. This stems from evidence gathered from the study participants, revealing the various challenges that are extant at the national and sub-national levels. While these challenges – healthcare workers’ knowledge deficiency and fear, poor technical infrastructure, poor reporting system, and inconsistency in government commitment – may appear mundane, they are critical to optimizing the AEFI surveillance system and maintaining the drive for an improved disease management system. Recommendation This study recommends that stakeholders at all levels should take up improved ownership of AEFI reporting (especially electronic) systems in the country.